Enhancement of synthesis of ZSM-11 zeolite by microwave irradiation - Azzolina Jury, Federico (2014)
A novel and complete description for ZSM-11 zeolite microwave-assisted synthesis is provided. The time required for the synthesis of ZSM-11 zeolite was remarkably reduced down to 3–4 days instead of 14 days under classical conditions, without the use of seed crystals and of any pretreatment step such as aging time. The crystallinity degree of ZSM-11 zeolites synthesized under microwave irradiation is considerably improved (39% higher) with respect to the crystallinity of conventional ZSM-11 zeolites. According to SEM images, the particle sizes of ZSM-11 zeolites synthesized by both methods are identical and a new morphology is observed when microwave irradiation is used. The surface area and microporous volume values for both synthesis methods are similar. In this work, the synthesis of ZSM-11 zeolite has been successfully intensified by using microwave irradiation. Energy consumption and synthesis time are considerably reduced.